Seasonal variation of Î´13C content in Porites coral from Simeulue Island waters for the period of 1993-2007 - Cahyarini, Sri Yudawati (Geological Agency, 2014)
DOI: 10.17014/ijog.v1i2.179Variation of Î´13C content in coral skeletons shows the influence of metabolic fractionation in aragonite coral. Understanding coral Î´13C variation can thus be useful to more understand e.g. past bleaching event which is further useful for coral health and conservation. In this study, Î´13C content in Porites coral from Labuhan Bajau, Simeulue Islands was analyzed. To know the correlation between variation of coral Î´13C and light intensity, the monthly variation of coral Î´13C is compared to solar radiation and cloud cover. The result shows that for the period of 2003 to 2008, coral Î´13C shows it is well correlated (r=0.42 p=0.153) with cloud cover variation in annual mean scale. Meanwhile, in seasonal mean variation, coral Î´13C is strongly influenced (r=0.85 p<0.0001) by cloud cover with 1 - 2 month time lag. Comparing to the solar radiation (cloud cover), SST influences dominantly the variation of coral Î´13C from southern Simeulue Island waters (LB sample) in an annual mean scale than in a seasonal scale.Â